Violência contra a mulher: uma análise do trabalho do Centro de Referência da Assistência Social - CREAS/Parnamirim - Oliveira, Valéria Regina Carvalho de (2009)
This work demonstrates the results obtained from research on violence against women: an analysis of the work from reference center of the Social Assistance-CREAS, held in the city of Parnamirim/RN from September 2008 extending through the february of 2009. Having as goal to investigate and examine in a longitudinal cut, which specifically covers the period from 2006 to 2007, find out extent the actions taken by the Reference Center Specialized Social Assistance-CREAS, contributed to the change of women who were there, by checking if there was any change in their positions ahead of the violence and if they began to realize how social subjects, able to control their living conditions and interfere in the orientation of social dynamics Have a particular emphasis on the presence of work and schooling or lack of them is also a factor to be allied to the barriers and rules imposed on women in contemporary society. In this study it was found through a qualitative research guided by dialectical and implemented through the use of documentary research, observation, semi-structured interview and an extensive theoretical background on the subject in question that the woman victim of violence is in a complex and contradictory context where there is both the construction and deconstruction of rights, a view that there are strong influences of patriarchal culture and the consequences of social issues that specifically searched for the public, focuses on social, economic , political, social and cultural. In this sense, the National Policy to Combat Violence against Women, operated by CREASE Parnamirim, is also reflected in its early stages in the life of these women are to nurture a real chance for these victims of violence, to perceive themselves as social subjects can control their lives and interfere in their own destinies. We want this study to add more knowledge to help and most appropriate intervention in this reality, but without the intention of reaching exhaustion, but to subsidize future studies on the topic of women victims of violence